Developing an Evidenced Based Intergenerational Pedagogy in Australia. Issue 1 (3rd April 2018) - Cartmel, Jennifer; Radford, Katrina; Dawson, Cindy; Fitzgerald, Anneke; Vecchio, Nerina
ABSTRACT: This paper presents a systematic literature review of the qualitative evidence in relation to intergenerational learning programs, principles, and practices. The aim of the review is to develop the evidence base to form an Intergenerational Model of Practice Framework based on the Early Years Learning Framework (EYLF). The EYLF comprises three inter-related elements: principles, practice, and outcomes. The results of this systematic literature review revealed commonalities across these elements and therefore what is needed to underpin the development of an evidence-based Intergenerational Model of Practice Framework.